Metakognisi Mahasiswa Dalam Menyelesaikan Masalah Pembuktian Matematis - Yudha, Sri Indah Dwirahmasari; Qohar , Abd; Sisworo, Sisworo (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2024)
Metacognition is one aspect that supports individual success in solving mathematical proof problems because using metacognition when solving problems will produce effective results. This research aims to collect information about students' metacognition in solving mathematical proof problems. This research applies a qualitative escriptive approach. There were 30 Mathematics Education students involved in this research from Universitas Negeri Malang. The way to obtain data in this research uses a mathematical proof test and interviews. The results obtained from this research reveal that the metacognition experienced by students consists of awareness, regulation, and evaluation. However, the metacognitive activities of the first student were different from other students. This is because each individual’s metacognition is different even though both have the same problem-solving abilities.